Regioselective Plasmon-Driven Decarboxylation of Mercaptobenzoic Acids Triggered by Distinct Reactive Oxygen Species - dos Santos Lopes, Douglas; dos Santos Abreu, Dieric; Ando, Rômulo Augusto; Corio, Paola (ACS catalysis, 2022)
The non-radiative decay of surface plasmon resonance (SPR) in plasmonic metal nanoparticles (NPs) opens up unique hot-carrier-driven chemical transformation mechanisms. Here, the hot-carrier generation of reactive oxygen species was demonstrated to trigger the regioselective plasmon-driven decarboxylation of mercaptobenzoic acid (MBA) isomers over Ag (AgNPs) and Au nanoparticles (AuNPs). Controlled catalytic experiments indicated that the catalytic C–C bond cleavage over AgNPs and AuNPs is primarily initiated by photogenerated singlet oxygen (1O2) and hydroxyl radical (•OH), respectively. Energetic hot electrons on AgNPs can successfully generate 1O2 from 3O2 via Dexter energy transfer, while hot holes generated under the Fermi level of AuNPs have sufficient energy to oxidize OH– and promote the formation of reactive •OH. The catalytic activity trend was evaluated considering the known ortho-substituent effect. The data discussed herein shed light on how the intrinsic differences in electronic energy levels and metal–molecule interactions precisely tune the regioselectivity of plasmon-driven transformations and may guide the rational design of plasmonic catalysts for distinct desired reactions.